(k/k+1)+ (1/(k+1)(k+2)) = (k+1)/(k+1)+1

I just need to make the left side equal to the right side. This is what I have:

k(k+2)/(k+1)(k+2) + 1/(k+1))k+2) =(k+1)/(k+1)+1

k(k+2)+1/(k+1)(k+2) = (k+1)/(k+1)+1

Printable View

- March 24th 2010, 01:36 PMmath61688Need help balancing an Induction Proof
(k/k+1)+ (1/(k+1)(k+2)) = (k+1)/(k+1)+1

I just need to make the left side equal to the right side. This is what I have:

k(k+2)/(k+1)(k+2) + 1/(k+1))k+2) =(k+1)/(k+1)+1

k(k+2)+1/(k+1)(k+2) = (k+1)/(k+1)+1 - March 24th 2010, 02:20 PMtonio
- April 24th 2010, 10:24 AMmath61688
thanks for the help!